A dainty review of the business and economic history of Chile and Latin America - Bátiz Lazo, Bernardo (Estudios de Economía, 2016)
This introductory piece provides some context to the special edition on business and economic history of Chile and Latin America. It also provides an introduction to better understanding research and method in business history while inviting for this field to be further developed in Chile.